Factors Influencing Fast-Food Consumption Among Adolescents in Tehran: A Qualitative Study - Askari Majabadi, Hesamedin (Iran Red Crescent Med J, 2016)
BACKGROUND: The consumption of different types of fast food is increasingly growing in all parts of the world, both in developed and developing countries. Because of the changes and transitions in the lifestyle and dietary habits of people, an increasing number of people from different age groups, particularly adolescents and young adults, are inclined toward consuming fast food. OBJECTIVES: The objective of this study was to investigate the factors influencing fast-food consumption among adolescents in Tehran, Iran. PATIENTS AND METHODS: The present qualitative study was conducted in 2012 - 2013 in Tehran, the capital of Iran. To achieve the objective of this study, 42 adolescents were enrolled in this study through a purposive sampling method, and the required data was collected via individual semi-structured in-depth interviews. Data collection and analysis were carried out simultaneously, and the collected data was analyzed via a thematic content analysis and using MAXQDA 10 software. RESULTS: In this study after coding the transcribed interviews, the findings were categorized into three main themes as follows: personal views, social factors, and family factors. Each theme included several categories and subcategories, and the coded sentences and phrases were placed under each category and subcategory. CONCLUSIONS: The results of this study showed that the number of factors promoting fast-food consumption appeared to be more than the inhibiting factors and that the diverse factors at the individual and social level influenced fast-food consumption among adolescents.